Manufacturing method of compression bonded magnets
A controlled manufacturing process for compressed bond magnets with specific magnet and resin ratios, combined with a heating-oriented magnetic field, achieves balanced magnetic performance and dimensional stability.
Patent Information
- Application Number
- JP2022512049
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-31
- Filing Date
- 2021-03-24
- Publication Date
- 2025-01-29
- Estimated Expiration
- 2041-03-24
AI Technical Summary
Existing compressed bond magnets face challenges in balancing residual magnetic flux density (BR) and reverse magnetic field (HK) due to variations in magnet and resin content and molding pressure, leading to incompatible performance characteristics.
A manufacturing method involving a specific composition of magnet powder and binder resin, with controlled magnet and resin ratios, along with a heating-oriented magnetic field compression process, to achieve optimal BR and HK balance.
The method produces compressed bond magnets with enhanced magnetic characteristics, ensuring high BR and HK values while maintaining dimensional accuracy and reducing particle cracking.
Smart Images

Figure 0007623600000002 
Figure 0007623600000003 
Figure 0007623600000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a compression bonded magnet. [Background technology]
[0002] Rare earth magnets are widely used in electromagnetic devices (electric motors, etc.) to improve performance and save energy. Rare earth magnets come in two types: sintered magnets made by sintering rare earth magnet powder, and bonded magnets made by binding rare earth magnet powder with a binder resin. Bonded magnets have a large degree of freedom in shape and are easier to mold than sintered magnets.
[0003] There are two main types of bonded magnets: injection bonded magnets, which are made by injecting a molten mixture of magnet powder and thermoplastic resin into the cavity of an electromagnetic component (such as the slots of a rotor core), and compression bonded magnets, which are made by compressing and molding a mixture or kneaded product of magnet powder and thermosetting resin in the cavity of a mold.Compression bonded magnets have better heat resistance than injection bonded magnets because they use thermosetting resin.
[0004] Compression bonded magnets are usually manufactured by high pressure molding of a compound with a reduced amount of resin and a higher amount of magnet powder (simply called "magnet amount") in order to improve magnetic properties (especially Br). The following Patent Document 1 describes such conventional compression bonded magnets. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 3731597 [Patent Document 2] JP 2006-49554 A Summary of the Invention [Problem to be solved by the invention]
[0006] Patent Document 1 proposes a compression bonded magnet with a magnet amount of 97.5-98.5 mass% (resin amount: 1.5-2.5 mass%) and a molding pressure of 392-892 MPa. The residual magnetic flux density (Br) of this compression bonded magnet is sufficiently large at 1.0 T, but the reverse magnetic field (Hk) that demagnetizes the Br by 10% is small at 280 kA / m. In this way, with a compression bonded magnet that is molded at high pressure with a small amount of resin and a large amount of magnet (about 98 mass%), Br and Hk are not compatible at a high level.
[0007] Incidentally, in contrast to such high-pressure molded bonded magnets, the above-mentioned Patent Document 2 describes a low-pressure molded bonded magnet. Patent Document 2 proposes a bonded magnet molded at a low pressure of 15 to 50 MPa, with a magnet amount of 96.5 to 97.0 mass% and a resin amount of 3 to 3.5 mass%, in order to reduce cogging torque, etc. However, even with such bonded magnets, the magnet amount is still large, making it difficult to achieve both Br and Hk at a high level.
[0008] The present invention has been made in view of the above circumstances, and has an object to provide a manufacturing method and the like that can obtain a compression bonded magnet that can achieve both Br and Hk at a high level. [Means for solving the problem]
[0009] As a result of intensive research by the inventors to solve this problem, they succeeded in obtaining a compression bonded magnet with a sufficiently large Hk, which is an index of effective magnetic flux density B against a reverse magnetic field, as well as Br, by setting the magnet amount and molding pressure (compressive force) within a range different from conventional ranges. By expanding on this result, they have completed the present invention, which will be described below.
[0010] <Manufacturing method of compression bonded magnets> (1) The present invention is a method for producing a compressed bonded magnet, comprising the steps of: placing a bonded magnet raw material, which is a compound in which magnet powder and a binder resin capable of binding the magnet powder are mixed in a granular form, or a preform of the compound, into a cavity; and compressing the bonded magnet raw material in the cavity in a heated, aligning magnetic field, The bonded magnet raw material has a mass ratio of the magnet powder to the total of the magnet powder and the binder resin of 90 to 95.7 mass%, the magnet powder comprises a coarse powder having an average particle size of 40 to 200 μm and a fine powder having an average particle size of 1 to 10 μm, the mass ratio of the coarse powder to the total of the coarse powder and the fine powder is 60 to 90 mass%, the coarse powder comprises hydrogen-treated rare earth anisotropic magnet powder, the binder resin comprises a thermosetting resin, and the molding process is performed at a compression force of 8 to 70 MPa and a heating temperature of 120 to 200°C, in this method for producing a compressed bonded magnet.
[0011] (2) Compression bonded magnets (also simply called "bonded magnets") obtained by the manufacturing method of the present invention exhibit excellent magnetic properties, achieving a high balance between Br and Hk. Hk represents the magnitude of the reverse magnetic field that reduces Br by 10%, and is an index of the effective magnetic flux density B against the reverse magnetic field.
[0012] Furthermore, in the molding process according to the present invention, the applied compressive force is low, so deformation (dimensional change) of the cavity or the case that constitutes the cavity is also small. Therefore, according to the manufacturing method of the present invention, it is easy to ensure dimensional precision for the bonded magnet itself, or for the magnetic member (field element, etc.) in which the bonded magnet is integrated with the case that constitutes the cavity.
[0013] Compression bonded magnets The present invention can also be understood as a compression bonded magnet. For example, the present invention may be a compression bonded magnet in which magnet powder is bound with a binder resin, the mass ratio of the magnet powder to the total of the magnet powder and the binder resin is 90 to 95.7 mass%, the magnet powder includes a coarse powder with an average particle size of 40 to 200 μm and a fine powder with an average particle size of 1 to 10 μm, the mass ratio of the coarse powder to the total of the coarse powder and the fine powder is 60 to 90 mass%, the coarse powder includes hydrogen-treated rare earth anisotropic magnet powder, and the binder resin includes a thermosetting resin.
[0014] The compression bonded magnet of the present invention can have a Br of, for example, 0.70 T (7.0 kG) or more, 0.72 T (7.2 kG) or more, 0.74 T (7.4 kG) or more, 0.76 T (7.6 kG) or more, 0.78 T (7.8 kG) or more, or 0.80 T (8.0 kG) or more, and an Hk of, for example, 535 kA / m or more, 540 kA / m or more, or even 545 kA / m or more.
[0015] Magnetic Members The present invention can also be understood as a magnetic member (electromagnetic member, etc.) in which a compression bonded magnet and a housing having a cavity are integrated together. One example of the magnetic member is a field element that includes a housing having a cavity and a compression bonded magnet filled (integrally molded) in the cavity.
[0016] The field element is, for example, the rotor or stator of an electric motor. Electric motors include not only motors but also generators. The electric motor may be a DC motor or an AC motor. When the field element is a rotor, for example, the housing is a rotor core and the cavity is a slot formed in the rotor core. The rotor may be an inner rotor or an outer rotor.
[0017] "others" Unless otherwise specified, "x to y" in this specification includes a lower limit value x and an upper limit value y. Any numerical value included in the various numerical values or numerical ranges described in this specification may be used as a new lower limit or upper limit value to create a new range such as "a to b". Furthermore, unless otherwise specified, "x to y μm" in this specification means x μm to y μm. The same applies to other unit systems (kA / m, kOe, etc.). [Brief description of the drawings]
[0018] [Figure 1] FIG. 1 is an explanatory diagram showing BH curves and JH curves and operating lines for three types of permanent magnets with different Br and Hk. [Diagram 2] FIG. 1 is a schematic diagram showing the relationship between Br distribution, magnet amount, and compression force of a bonded magnet. [Diagram 3]It is a scatter diagram showing the magnet amount and compressive force of each bonded magnet according to the embodiment, and their Br and Hk. [Figure 4A] It is an SEM image observing the cross section of the bonded magnet according to Sample 24. [Figure 4B] It is an SEM image observing the cross section of the bonded magnet according to the comparative sample. [Diagram 5] It is an external photograph of a rotor for IPM in which a bonded magnet is integrally formed in a slot. [Figure 6] It is a cross-sectional view showing a part of a rotor core used to compare the orientation rates of a bonded magnet formed by low-pressure compression molding and a bonded magnet formed by injection molding.
Mode for Carrying Out the Invention
[0019] One or two or more constituent elements arbitrarily selected from the matters described in this specification can be added to the configuration of the present invention described above. The constituent elements related to the manufacturing method can also be the constituent elements related to the product. Whether any embodiment is the best depends on the object, required performance, etc.
[0020] 《Evaluation Indexes of Bonded Magnets / Br, Bd, Hk》 In order to ensure the output of an electromagnetic device (for example, an electric motor) composed of a field magnet and an armature, generally, for the permanent magnet used for the field magnet, not only the residual magnetic flux density (simply referred to as "Br"), but also the operating point magnetic flux density (simply referred to as "Bd") is required to be large. Regarding this point, taking the permanent magnet used for the rotor of an interior permanent magnet synchronous motor (IPM / simply referred to as "motor") as an example, it will be described with reference to FIG. 1. FIG. 1 shows the magnetization curve (J-H curve), the demagnetization curve (B-H curve), and the operating line (permeance straight line / Pc: permeance coefficient) for three types of permanent magnets ("Magnet 1", "Magnet 2", "Magnet 3") having different magnetic characteristics. The Br, Bd, and Hk of each magnet are shown with corresponding subscripts (1 to 3). FIG. 1 shows the case where the magnetic characteristics of each magnet are Br1 = Br2 < Br3, and Magnet 1 has the best rectangularity.
[0021] When the motor is in operation, an opposing magnetic field (Hex) is applied from the armature to the permanent magnets in the rotor. At this time, Bd1>Bd3>Bd2. In other words, magnet 1, which has excellent rectangular shape, has a larger Bd than magnet 3, which has a larger Br. However, this Bd varies depending on the permeance coefficient Pc, which is determined from the motor specifications, and the current range, which is determined by the motor's application, operating conditions, etc. Therefore, Bd is not necessarily an appropriate index for evaluating the physical properties (magnetic characteristics) of the permanent magnet itself.
[0022] Therefore, in this specification, permanent magnets (bonded magnets) are evaluated using Br, an index of magnetization potential, and Hk, an index of reverse magnetic field resistance that is independent of the specifications (data, etc.) of electromagnetic equipment (motors, etc.). As mentioned above, Hk is the magnitude of the reverse magnetic field when the residual magnetic flux density Br of a bonded magnet drops by 10%. Hk is related to the supply of effective magnetic flux density B when a reverse magnetic field acts from the armature.
[0023] For example, when Hk is calculated from the JH curves of each magnet shown in Figure 1, Magnet 1, which has excellent squareness, has a much larger Hk than Magnet 3, which has a large Br. In other words, Hk can be seen to be an accurate indicator of squareness, an important property of bonded magnets used in motors, etc.
[0024] Bonded magnet raw materials The bonded magnet raw material may be a compound or a preform of a compound.
[0025] The compound is made of granules of a mixture of magnet powder and binder resin. The mixing process is preferably performed at a temperature (called the "mixing temperature") that is at least equal to or higher than the temperature at which the binder resin softens (glass transition point) and lower than the temperature at which the thermosetting resin contained in the binder resin hardens (hardening temperature). Depending on the type and composition of the binder resin (especially the thermosetting resin), the mixing temperature is preferably, for example, 40 to 120°C, or even 80 to 100°C.
[0026] The mixing may be performed, for example, under heating without applying pressure. Even when using a batch-type kneader, for example, the compound may be added in an amount of 75% or less, or even 65% or less, of the processing volume of the processing tank, and the compound may be heated and mixed by rotating the blades without applying pressure.
[0027] The preform consists of a block of the above-mentioned compound in a specified form (shape, size). If the preform has a form similar to that of a bonded magnet, the containing process can be carried out efficiently. The preform may also have a form dissimilar to that of a bonded magnet. For example, it may be a divided body that has been subdivided to the extent that it can be filled or loaded into a cavity. In this case, there is no need to prepare a dedicated preform for each bonded magnet, which increases the versatility of the preform.
[0028] The preforming process should also be performed under conditions that are unlikely to cause damage such as cracks to the magnet particles. For example, the compound should be pressurized at 2 MPa or less, or even 0.5 MPa or less to perform preforming. Note that preforming is usually performed by pressurizing the compound filled in a cavity separate from the cavity in which the bonded magnet is molded.
[0029] 《Magnetic Powder》 The magnet powder includes coarse powder and fine powder having different average particle sizes, and the coarse powder includes hydrogen-treated rare earth anisotropic magnet powder.
[0030] The average particle size of the coarse powder is, for example, 40 to 200 μm, or 80 to 160 μm. The average particle size of the fine powder is, for example, 1 to 10 μm, or 2 to 6 μm. The average particle size referred to in this specification is determined by measurement (measurement using the Fraunhofer method) using a laser diffraction type particle size distribution measuring device (HELOS manufactured by Nippon Laser Corporation).
[0031] The mass ratio of the coarse powder to the total of the coarse powder and the fine powder (or the entire magnet powder) is, for example, 60 to 90 mass%, or 75 to 85 mass%, in other words, the mass ratio of the fine powder to the total is, for example, 10 to 40 mass%, or 15 to 25 mass%.
[0032] The mass percentage of the entire magnet powder relative to the entire bond magnet raw material (bond magnet) (total of magnet powder and binder resin) is, for example, 90 to 95.7 mass%, 91 to 95 mass%, 91.5 to 94.5 mass%, 92 to 94 mass%, or even 92.5 to 93.5 mass%. If the amount of magnet is too small (for example, less than 90 mass%), the resin will seep out from the clearance between the die and punch during molding, making it easier for burrs to form. If the amount of magnet is too large (for example, more than 95.7 mass%), Hk will drop sharply. This tendency is noticeable in areas where the compression force is excessive (for example, more than 70 MPa).
[0033] By keeping the particle size and ratio of the coarse powder and fine powder, and the amount of magnet (amount of resin) relative to the entire bonded magnet raw material (bonded magnet) within specified ranges, a bonded magnet with excellent magnetic properties (residual magnetic flux density Br, Hk, etc.) can be obtained even when molded at low pressure.
[0034] Various magnet powders can be used for the coarse powder and fine powder. According to the manufacturing method of the present invention, even when the coarse powder contains hydrogen-treated rare earth anisotropic magnet powder, cracking of the magnet particles is suppressed. Hydrogenation mainly involves a disproportionation reaction due to hydrogen absorption (also simply called the "HD reaction") and a recombination reaction due to desorption of hydrogen (also simply called the "DR reaction"). The HD reaction and the DR reaction are collectively referred to simply as the "HDDR reaction." Furthermore, the hydrogen treatment that causes the HDDR reaction is simply referred to as the "HDDR (treatment)."
[0035] In addition, unless otherwise specified, HDDR as used in this specification also includes an improved type, d-HDDR (dynamic-Hydrogenation-Disproportionation-Desorption-Recombination). d-HDDR is described in detail, for example, in International Publication WO2004 / 064085.
[0036] An example of the coarse powder is NdFeB-based anisotropic magnet powder, the base components of which are Nd, Fe, and B. An example of the fine powder is SmFeN-based anisotropic magnet powder, the base components of which are Sm, Fe, and N, or SmCo-based anisotropic magnet powder, the base components of which are Sm and Co.
[0037] As the fine powder (part), NdFeB-based anisotropic magnet powder with particle size adjustment may be used. Furthermore, as part of the magnet powder, magnet powders other than rare earth anisotropic magnet powder (rare earth isotropic magnet powder, ferrite magnet powder, etc.) may be included. In addition, the base component referred to in this specification can be said as an essential component or a main component. The total amount of the elements that are the base component is usually 80 atomic % or more, 90 atomic % or more, 93 atomic % or more, or even 95 atomic % or more with respect to the entire target object (magnet particles). In addition, the rare earth magnet powder may contain elements (heavy rare earth elements such as Dy and Tb, Cu, Al, Co, Nb, etc.) that increase the coercive force and heat resistance of the rare earth magnet powder.
[0038] <Binder resin> The binder resin contains a thermosetting resin, which improves the heat resistance of the bonded magnet. Thermosetting resins include epoxy resin, phenol resin, melamine resin, urea resin, and unsaturated polyester resin. A typical epoxy resin is usually a mixture of a prepolymer and a hardener, and hardens by forming a crosslinked network with epoxy groups. Examples of epoxy resin prepolymers include novolac type, bisphenol A type, bisphenol F type, biphenyl type, naphthalene type, aliphatic type, and glycidyl amine type. Examples of epoxy resin hardeners include amine type, phenol type, and acid anhydride type.
[0039] When a one-part epoxy resin is used, the time of thermal hardening can be adjusted by the curing treatment (thermal hardening process), enabling efficient batch processing, etc. The curing treatment is carried out, for example, by heating the bonded magnet after the molding process to 130 to 250°C, or even 150 to 230°C.
[0040] Incidentally, each magnet particle may be coated with a surfactant suitable for the binder resin. This can improve the orientation variability of the magnet particles in the softened or molten resin, and the bonding between the magnet particles and the resin. When an epoxy resin is used, for example, a titanate coupling agent or a silane coupling agent can be used as the surfactant. The thickness of the surfactant layer may be about 0.1 to 2 μm.
[0041] 《Molding process》 The bonded magnet raw material contained in the cavity is compressed in a heating and aligning magnetic field to obtain a bonded magnet of the desired shape. The compression force (molding pressure) is, for example, 8 to 70 MPa, 10 to 65 MPa, 15 to 60 MPa, 20 to 50 MPa, or even 30 to 40 MPa.
[0042] If the compression force is too small (e.g., less than 8 MPa), the Br and relative density of the bonded magnet will decrease. If the compression force is too large (e.g., more than 70 MPa), the Hk will decrease. This tendency is more noticeable in areas where the magnet amount is excessive (e.g., more than 95.7 mass% magnet powder). Furthermore, excessive compression force can lead to increased deformation of the cavity and cracking of the magnet particles.
[0043] Incidentally, it was previously thought that the higher the compression force and the greater the amount of magnet, the greater the Br of the bonded magnet, as shown in Figure 2. However, the inventors discovered that even in the low-pressure region where the compression force is less than 100 MPa, by setting the magnet amount to 90-96 mass%, a bonded magnet that exhibits a high peak Br can be obtained, and this led to the completion of the present invention.
[0044] The heating temperature during the molding process is, for example, 120 to 200°C, or even 130 to 170°C. If the heating temperature is too low, the binder resin will not soften or melt sufficiently, which may lead to cracking of the magnet particles, a decrease in the degree of orientation, etc. If the heating temperature is too high, oxidation deterioration of the magnet particles and hardening of the thermosetting resin may progress.
[0045] The aligning magnetic field during the molding process is usually applied in an aligning direction that intersects with the compression direction of the bonded magnet raw material. The magnitude of the aligning magnetic field is, for example, 0.5 to 3 T, or even 1 to 2 T. The aligning magnetic field is the magnetic flux density on the inner peripheral surface of the cavity in which the bonded magnet is molded. In addition to electromagnets, rare earth permanent magnets may also be used as the magnetomotive source of the aligning magnetic field.
[0046] Bonded Magnets The bonded magnet may have a relative density of, for example, 90% or more, 95% or more, or even 98% or more. The upper limit of the relative density is 99.5% or even 100%. Note that the relative density (ρ / ρ 0 ) is the theoretical density (ρ 0 ) is the ratio (percentage) of the actual density (ρ) to the theoretical density (ρ 0 ) is determined from the true density of the magnetic powder and binder resin that make up the bonded magnet and the amount of each mixed together. The real density (ρ) is determined from the mass and volume obtained by measuring the bonded magnet after molding (and curing). The volume can be determined using the Archimedes method, but it is sufficient to calculate it from the shape (dimensions) of the molded body.
[0047] The bonded magnet may be magnetized (magnetizing magnetic field: 2 to 6 T) before or after the curing process.
[0048] Magnetic Members Bonded magnets are used in a variety of magnetic components. Bonded magnets are molded integrally within the cavity of a housing (such as a rotor core), allowing for efficient manufacturing of magnetic components. Low-pressure molding of bonded magnets also suppresses deformation of the housing that forms the cavity. This allows for greater freedom in the design of the housing and improves the precision of the magnetic components. A typical example of such a magnetic component is the field magnet of an electric motor (vehicle drive motors, air conditioners, motors for home appliances, etc.). EXAMPLES
[0049] A number of samples (compression bonded magnets) were produced with different magnet amounts (resin amounts) and compression forces, and their properties were measured and evaluated. Based on these specific examples, the present invention will be described in detail below.
[0050] <Sample Preparation> (1) Magnet powder and binder resin The magnet powders used were a commercially available NdFeB-based anisotropic magnet powder (Magfine, manufactured by Aichi Steel Corporation; Br / Br: 1.28 T, iHc: 1313 kA / m, average particle size: 125 μm), which is a coarse powder produced by hydrogen treatment (d-HDDR), and a commercially available SmFeN-based anisotropic magnet powder (SmFeN alloy fine powder, manufactured by Sumitomo Metal Mining Co., Ltd.; C / Br: 1.35 T, iHc: 875 kA / m, average particle size: 3 μm), which is a fine powder.
[0051] As the binder resin, a thermosetting epoxy resin (NC-3000L manufactured by Nippon Kayaku Co., Ltd.) was prepared. The softening point of this resin was 60°C.
[0052] (2) Bonded magnet raw materials A bonded magnet raw material was prepared by mixing magnet powder, which was weighed out as coarse powder and fine powder in a ratio of 8:2 (almost the same in terms of mass ratio / volume ratio), with binder resin in the ratio shown in Table 1. The amount of magnet shown in Table 1 is the mass ratio of the magnet powder to the entire mixture (bonded magnet raw material) consisting of the magnet powder (coarse powder and fine powder) and binder resin.
[0053] The magnet powder and the binder resin were mixed for 5 minutes in a non-pressurized state with the kneader rotating at a low speed (10 rpm). At this time, the kneader's temperature was kept at 90° C. In this way, a compound in which the magnet powder and the binder resin were melted and mixed was obtained (melt mixing process).
[0054] (3) Molding The compound was loaded into the cavity of a mold (containing process) and compression molded in a heated orienting magnetic field (molding process). At this time, the temperature of the mold (inner wall surface of the cavity): 150°C, the orienting magnetic field: 955kA / m, and the orientation direction was a direction (radial direction) perpendicular to the compression direction (axial direction). The compression force was changed for each sample as shown in Table 1.
[0055] Note that a preformed compound may be used to integrally mold a bonded magnet into the slots of a rotor core, etc. The preformed compound is obtained, for example, by filling a cavity whose cross-sectional shape is slightly smaller than the slots, etc., with the compound and applying pressure (preformed process).
[0056] (4) Cure treatment The compression molded body of the bonded magnet raw material was removed from the cavity of the mold and heated in air at 150°C for 30 minutes. In this way, bonded magnets (each sample shown in Table 1) in which the binder resin was thermally cured were obtained.
[0057] (5) Magnetization Each bonded magnet was magnetized by applying a magnetic field of 6 T to the magnet using an air-core coil.
[0058] Measurement and Observation (1) Magnetic properties The magnetic properties of each sample were measured at room temperature using a DC BH tracer (TRF-5BH-25Auto manufactured by Toei Kogyo Co., Ltd.) The Br and Hk obtained from the BH curves are also shown in Table 1.
[0059] (2) Observation The cross section of the bonded magnet for each sample was observed with a scanning electron microscope (SEM). The SEM images were used to determine whether or not there were cracks in the magnetic particles of the coarse powder (NdFeB anisotropic magnet powder). The results are also shown in Table 1. SEM images of sample 24 and a comparative sample described below are shown in Figures 4A and 4B (collectively referred to as "Figure 4").
[0060] "evaluation" For each sample shown in Table 1, the magnet amount is plotted on the horizontal axis and the compressive force on the vertical axis, and the contour lines relating to Br and Hk are shown in Figure 3. The iso-Br lines are plotted in increments of 0.01 T, and the iso-Hk lines are plotted in increments of 5 kA / m. However, for the sake of convenience, the iso-Br lines below 0.70 T are plotted in increments of 0.05 Br.
[0061] (1)Br As is clear from Figure 3, Br increased as the compressive force increased. When the compressive force became 10 MPa or less, Br began to decrease rapidly, and was less than 0.7 T at less than 8 MPa. Also, contrary to conventional technical common sense, when the compressive force was 8 to 110 MPa and further 10 to 100 MPa, Br peaked at around 93 mass% of the magnet amount. It can also be seen that when the compressive force became a low pressure region from around 10 MPa, the magnet amount at which Br peaked shifted from around 93 mass% to around 90 mass%.
[0062] (2)Hk As is clear from Figure 3, Hk decreased as the compressive force increased. Hk also decreased as the amount of magnet increased. In particular, when the amount of magnet exceeded 95.7 mass%, Hk decreased rapidly.
[0063] (3) Magnet quantity When the magnet amount was 89.6% by mass, even with a compression force of 5 MPa or 10 MPa, resin leaked out from the clearance between the die and punch, causing burrs. In order to avoid damaging the molding machine, molding was not performed with a compression force higher than 89.6% by mass of the magnet.
[0064] From the above results, for example, when Br is 0.7 T or more and Hk is 535 kA / m or more, the magnet amount should be 90 to 95.7 mass % and the compression force should be 8 to 70 MPa.
[0065] (4) Cross section As is clear from Figure 4A, in the bonded magnet of sample 24 (magnet amount: 93.1 mass%, compression force: 30 MPa), even the coarse magnet particles with a particle size of 100 μm are not cracked. The internal crack to the right of the coarse magnet particle in the center of the photo has not progressed either.
[0066] As is clear from Figure 4B, in the comparative sample (magnet amount: 95.0 mass%, compression force: 200 MPa), many of the magnet particles had cracks. This is thought to be because the compression force was too large compared to the magnet amount. The comparative sample was produced in the same way as the other samples, except for the magnet amount and compression force.
[0067] (5) Discussion From the above, when the amount of magnet and the compression force are within a specific range, it is possible to achieve both Br and Hk at a high level. The reason for this is presumed to be as follows. In the manufacturing method of the present invention, the amount of resin is relatively large and molding is performed at low pressure. Therefore, even with coarse magnet particles, posture change is easy, sufficient orientation is ensured, and they are less likely to break. As a result, it is thought that high Br and high Hk can be achieved even if the content of coarse magnet powder, which is the main source of magnetic force, is relatively small.
[0068] In particular, it is believed that the high Hk is achieved by suppressing the disturbance of the orientation of the magnet particles and the localized deterioration of magnetic properties that accompanies the generation of new surfaces due to cracks in the magnet particles. In this way, it is believed that the JH curve of the bonded magnet is prevented from becoming steeper from the Br point compared to the JH curve of the raw material magnet powder, and thus the sudden decrease in Hk is also suppressed.
[0069] Rota (1) The bonded magnet shown in Sample 24 was integrally molded (low pressure compression molded) into the slot (cavity) of the rotor core (housing / electromagnetic component) of an embedded permanent magnet synchronous motor (IPM). The appearance of the rotor (field element) thus obtained is shown in Figure 5. The rotor core is made of a laminate of silicon steel sheets punched into the desired shape.
[0070] Because the compressive force of the bonded magnet was small, there was almost no deformation even in the thin-walled parts on the outer periphery of the slot. It was also confirmed that a rotor for IPM with high precision (roundness, cylindricity) could be obtained.
[0071] (2) As shown in Figure 6, the orientation rate of low-pressure compression molded bonded magnets and the orientation rate of injection molded bonded magnets were determined for the multi-layer slots (inner diameter side slots and outer diameter side slots) provided in each pole of the rotor core (8 magnetic poles). Note that the orientation rate here is the ratio (Brx / Br0) of the residual magnetic flux density (Brx) when an orienting magnetic field of x kA / m is applied to the residual magnetic flux density (Br0) when an orienting magnetic field of 1591 kA / m (20 kOe) is applied.
[0072] The compression molding was performed under the same conditions as those of Sample 24. The injection molding was performed using the above-mentioned magnet powder (coarse powder:fine powder=8:2) and binder resin (PPS:9.2% by mass) at an injection pressure of 150 MPa. The temperature of the rotor core during molding was 150°C for both cases.
[0073] When low-pressure compression molding was used, the orientation rate was higher on both the outer diameter side and the inner diameter side than when injection molding was used. As an example, when an orientation magnetic field (x) of 955 kA / m was applied to the rotor outer diameter side cavity and an orientation magnetic field (x) of 637 kA / m was applied to the rotor inner diameter side cavity, the orientation rate of low-pressure compression molding was outer diameter side bonded magnet: 99% / inner diameter side bonded magnet: 97%, while the orientation rate of injection molding was outer diameter side bonded magnet: 95% / inner diameter side bonded magnet: 93%. Even with the same orientation magnetic field, it was found that when low-pressure compression molding was used, not only did the orientation rate increase overall, but the decrease in the orientation rate of the inner diameter side bonded magnet (where the orientation magnetic field decreases) relative to the outer diameter side bonded magnet was also suppressed.
[0074] For these reasons, by using a bonded magnet that has been subjected to low-pressure compression molding in the rotor, it is possible to expect an improvement in motor torque, even when the same magnetic field is generated in the stator, compared to when injection molding is used.
[0075] [Table 1]
Claims
1. a step of placing a bond magnet raw material, which is a compound in which magnet powder and a binder resin capable of binding the magnet powder are mixed in a granular form or a preform of the compound, into the cavity; a molding step of compression molding the bonded magnet raw material in the cavity in a heating and aligning magnetic field; A method for producing a compression bonded magnet comprising: The bonded magnet raw material has a mass ratio of the magnet powder to the total of the magnet powder and the binder resin of 90 to 95.7 mass %, the magnet powder comprises a coarse powder having an average particle size of 40 to 200 μm and a fine powder having an average particle size of 1 to 10 μm, the mass ratio of the coarse powder to the total of the coarse powder and the fine powder being 60 to 90 mass %, The coarse powder comprises a hydrogen-treated rare earth anisotropic magnet powder; The binder resin includes a thermosetting resin, The molding step is performed at a compression force of 8 to 70 MPa and a heating temperature of 120 to 200°C. The method for manufacturing a compression bonded magnet provides a field element in which the compression bonded magnet is integrated into a housing having the cavity.
2. The coarse powder contains NdFeB-based anisotropic magnet powder containing Nd, Fe, and B as base components, 2. The method for producing a compressed bonded magnet according to claim 1, wherein the fine powder contains SmFeN based anisotropic magnet powder having Sm, Fe and N as base components and / or SmCo based anisotropic magnet powder having Sm and Co as base components.
3. 3. The method for producing a compression bonded magnet according to claim 1, wherein the thermosetting resin is an epoxy resin.
4. 4. The method for producing a compressed bonded magnet according to claim 1, wherein the aligning magnetic field during the compacting step is 0.5 to 3 T and is applied in an orientation direction that intersects with the compression direction of the bonded magnet raw material.
5. The method for producing a compression bonded magnet according to any one of claims 1 to 4, wherein the compound is obtained by mixing the softened or melted binder resin with the magnet powder.
6. the housing is a rotor core of an electric motor, The method for producing a compressed bonded magnet according to any one of claims 1 to 5, wherein the cavities are slots provided in the rotor core.
Citation Information
Patent Citations
Manufacture of anisotropic bond magnet
JP1997330842A
Manufacture of material powder for anisotropic permanent magnet
JP1998189319A
Bonded magnetic having superior thermal stability, and its manufacturing method
JP2002175909A
Hybrid rare earth bonded magnet, compression molding equipment in magnetic field, and motor
JP2004296874A
Manufacturing method of polar anisotropy rare earth bond magnet and permanent magnet motor
JP2006049554A